Corporate control and executive selection - Francesco Lippi; Fabiano Schivardi (Quantitative Economics, 2014)
In firms with concentrated ownership the controlling shareholder may pursue nonmonetary private returns, such as electoral goals in a firm controlled by politicians or family prestige in family firms. We use a simple theoretical model to analyze how this mechanism affects the selection of executives and, through this, the firm's productivity compared to a benchmark where the owner only cares about the value of the firm. We discuss identification and derive two structural estimates of the model, based on different sample moments. The estimates, based on a matched employer–employee data set of Italian firms, suggest that private returns are larger in family- and government-controlled firms than in firms controlled by a conglomerate or by a foreign entity. The resulting distortion in executive selection can account for total factor productivity differentials between control types of up to 10%.
Keywords: 330; Corporate governance; private returns; total factor productivity